Reflections on the Foundations of Medical Liability for Wrongful Life. Life as harm? - Moreno More, César Edwin (2023)
The frustration of the expectations generated by the incessant advance of medical science and technology has led to a constant search for compensation. In this context, legal actions known as wrongful birth and wrongful life have been presented regarding the birth of minors with disabilities. While the former are recognized in the legal systems where these actions have been raised, the latter are generally denied, generating various doubts and questions. In this research, the arguments used in different legal systems to deny the acceptance of wrongful life actions are analyzed, questioning their foundation. This topic is especially complex not only from a legal standpoint but also primarily from a bioethical perspective, as its analysis involves an appreciation of the value of human life itself. In its development, we have used a qualitative research method, paying attention to the different legal systems of both civil law and common law. The research is divided into two parts: The first contextualizes the problem and the second focuses on its development, describing the origin and evolution of wrongful life actions, their circulation in various legal systems, their general denial in most of them and the critical analysis of the arguments manifested to deny their recognition.